PANDANGAN MASYARAKAT TERHADAP PROSESI TRADISI BETANGAS PERSPEKTIF ‘URF (Studi Kasus di desa Pasir Panjang Kecamatan Mempawah Timur Kabupaten Mempawah) - Ilham Nasrudin; Masrokhin Masrokhin (Kampus Akademik Publiser, 2024)
The Betangas tradition is one of the Malay traditions in Pasir Panjang village. The Betangas tradition is bathing using steam from boiled natural spices. The benefits are that it cleans dirt from the body, removes unpleasant odors from the body, and can refresh the body of the bride and groom during the wedding ceremony. This research has the following objectives: First, to find out the community's views on the Betangas traditional procession. Second, to find out the 'urf perspective on the Betangas traditional procession. In this research the author used a descriptive qualitative research method and used a sociological or empirical approach. Then the way to obtain data in the field is through interviews, observation and documentation. The results of this research conclude that in the view of the people in Pasir Panjang village regarding the Betangas traditional procession, namely that the Betangas tradition has existed since the time of the ancestors of the people of Pasir Panjang village, and has been passed down from generation to generation, this tradition is usually carried out before the wedding. The 'urf perspective regarding the Betangas tradition has two different legal views, namely between the Betangas tradition and the procession. The Betangas tradition in the 'urf perspective is seen as 'urf authentic, because this tradition does not bring harm. Meanwhile, the view on the Betangas procession from the perspective of 'urf is seen as 'urf fasid because in the procession Betangas have the habit of wearing clothes that are not good, and violate the rules of sharia'.